Sources of noise and their effects on nurses in intensive care units: A cross sectional study - Zahra Kooshanfar; Sadra Ashrafi; Ezzat Paryad; Yalda Salmanghasem; Tahereh Khaleghdoost Mohammadi; Ehsan Kazemnezhad Leili; Seyyed Mohammad Javad Golhosseini (Elsevier, 2022)
Background: Noise is a serious threat to the health of people. In Intensive Care Units (ICU), the higher level of noise may negatively affect the health of the patients and health care staff. Objectives: To determine the sources of noise and the related adverse effects from the ICU nurses' viewpoints. Methods: The study sample included all nurses (148) working in ICUs. The data collection tool was a three-section questionnaire. The first section was related to personal- occupational characteristics. The second part evaluated internal and external noise sources from the nurses' viewpoints. The third section assessed the effect of noise on four domains: physiology, emotions, subjective perception, and performance. The data were analyzed by SPSS version 22, using descriptive and inferential statistics. Results: The results showed that the major internal sources of noise were monitoring alarms and ventilators (61.5%).The highest and lowest mean ± SD of the scores about the effect of noise on the study domains were related to physiology (16.1 ± 4.8) and performance (14.9 ± 5.25). The three domains' scores (subjective perception, emotions, physiology) had significant relationship with the bed occupancy rate, the type of ICU, and the number of beds (P < 0.05). Also, the performance domain's scores had a significant relationship with work experience, bed occupancy rate, and shift type (P < 0.05). Conclusions: Since ambient noise is a threat to health and disturbs the patients and ICU staff, we believe that proper strategies should be designed to reduce its levels.